2014
DOI: 10.1021/ic402528j
|View full text |Cite
|
Sign up to set email alerts
|

Heteroleptic Bis(cis-1,2-disubstituted ethylene-1,2-dithiolato)nickel Complexes Obtained by Ligand-Exchange Reaction: Synthesis and Properties

Abstract: The ligand-exchange reaction has been investigated to synthesize nickel bis(dithiolene) complexes bearing one hydroxyl functional group aimed at being grafted thereafter onto polymer materials. This reaction leads easily to heteroleptic complexes with the ethylene-1,2-dithiolato core substituted by either alkyl or aryl moieties. Details on synthetic parameters are given. A direct link between the electronic properties of the obtained molecules and those of the parent complexes involved in the ligand-exchange r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Annealing at high temperatures led to a decrease in absorbance at short wavelengths and a slight increase and red‐shift in the absorbance at high wavelengths. The higher ratios of the long‐wavelength absorbance peak to the short‐wavelength absorbance peaks for the films annealed at higher temperatures suggest that MLCT and d‐π conjugation between Ni atoms and ethenetetrathiolate ligands are much stronger in the annealed films 24. The red‐shift at long wavelengths after annealing at 150 or 200 °C results in a decrease in bandgap estimated from the Tauc plots from 0.53 to 0.46 eV, which could lead to an increase in carrier density and electrical conductivity 1…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Annealing at high temperatures led to a decrease in absorbance at short wavelengths and a slight increase and red‐shift in the absorbance at high wavelengths. The higher ratios of the long‐wavelength absorbance peak to the short‐wavelength absorbance peaks for the films annealed at higher temperatures suggest that MLCT and d‐π conjugation between Ni atoms and ethenetetrathiolate ligands are much stronger in the annealed films 24. The red‐shift at long wavelengths after annealing at 150 or 200 °C results in a decrease in bandgap estimated from the Tauc plots from 0.53 to 0.46 eV, which could lead to an increase in carrier density and electrical conductivity 1…”
Section: Resultsmentioning
confidence: 99%
“…For fabrication of the P(Na X [Niett]) thin films, sodium methoxide (NaOCH 3 , 95% Sigma‐Aldrich), 1,3,4,6‐tetrathiapentalene‐2,5‐dione (TPD, >98.0% TCI), nickel(II) chloride hexahydrate, (NiCl 2 ∙6H 2 O, 99.9% Wako), and super dehydrated methanol (MeOH ≥99.8% Wako) were purchased commercially and used without further purification. The P(Na X [Niett]) was synthesized according to a modified procedure from literature as follows18,19,24,60: First, TPD (21 mg, 1.0 eq) and NaOCH 3 (25–27.5 mg, 4.5–5.0 eq) were dissolved in MeOH (2 mL) and stirred using a magnetic stirrer for 30 min at 80 °C in a nitrogen‐filled glove box for formation of tetrasodium ethenetetrathiolate. Next, NiCl 2 ·6H 2 O (24 mg, 1.0 eq) was added and stirred for 30 min at 80 °C to yield a dark brown P(Na X [Niett]) MeOH sol–gel solution (see Note S1, Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…Scheme 33 shows a selection of cyclic and heterocyclic systems pre-pared from the condensation of nucleophiles on various benzils. 54,[57][58][59][60]62,63 Functionalized quinoxalines, which represent an important class of nitrogen-containing heterocycles with a broad spectrum of biological properties, such as antitumor activities, 52,53 have been well studied. One of the most common strategies for their synthesis utilizes the condensation of o-phenylenediamines with benzil derivatives.…”
Section: Access To Various Heterocyclesmentioning
confidence: 99%
“…Finally, beside the syntheses of organic heterocycles starting from benzil substrates, Moineau-Chane Ching also demonstrated that heteroleptic nickel complexes having optical properties could be prepared rapidly with diaryl 1,2-diketones. 63 Functionalized benzils were reacted with P 4 S 10 to give their dithione sulfur analogues, which were transformed into homoleptic Ni complexes in the presence of NiCl 2 . Further ligand-exchange reactions between two different homolytic complexes furnished the desired heteroleptic-Ni complexes having a possible potential as conjugated materials for organic field-effect transistors and organic solar cells.…”
Section: Short Review Syn Thesismentioning
confidence: 99%
“…The reactivity of some members of this class of metal complexes was also explored. 44,46 Naphthalene-and coumarin-substituted dithiolene ligands were exploited as selective markers of the Ni 2+ ion. 47 Following our previous studies on d 8 metal complexes bearing Ar-edt 2− ligands showing potential-controlled spectroscopic and second-order NLO properties, 48,49…”
Section: ■ Introductionmentioning
confidence: 99%